Immunotherapy and Radiation Therapy for Non-Small Cell Lung Cancer—A Stimulating Partnership - Dams, Ritchell van; Yuan, Ye; Robinson, Clifford G.; Lee, Percy (Seminars in Respiratory and Critical Care Medicine, 2020)
Non-small cell lung cancer (NSCLC) is the most common subtype of lung cancer and the leading cause of cancer-related death. Although durable local control rates are high after surgical resection or definitive radiotherapy for early-stage disease, a substantial proportion of these patients eventually experience regional and/or distant failure and succumb to their metastatic disease. The discovery of immunotherapeutics and targeted biologics has revolutionized the treatment of locally advanced and metastatic disease, improving progression-free and overall survival when incorporated with the current standards of care. Notably, post-hoc analyses and early clinical trials provide a growing body of evidence to support a synergistic effect between radiation and immunotherapy for the treatment of NSCLC from early-stage to metastatic disease. Radiotherapy appears to be capable of not only potentiating the effect of immunotherapy in targeted lesions, but also eliciting an antitumor response in distant lesions without any direct exposure to radiation. This review explores the biologic basis of immunotherapy, targeted biologics, and radiotherapy as well as the preclinical and clinical data that support the combined use of radioimmunotherapy for early-stage, locally advanced, and metastatic NSCLC.
Keywords: non-small cell lung cancer; NSCLC; SBRT; Immunotherapy; biologics